Slope-Scale Remote Mapping of Rock Mass Fracturing by Modeling Cooling Trends Derived from Infrared Thermography - Federico Franzosi; Chiara Crippa; Marc-Henri Derron; Michel Jaboyedoff; Federico Agliardi (Remote Sensing, 2023)
The reliable in situ quantification of rock mass fracturing and engineering quality is critical for slope stability, surface mining and rock engineering applications, yet it remains difficult due to the heterogeneous nature of fracture networks. We propose a method to quantify and map the slope-scale geomechanical quality of fractured rock masses using infrared thermography (IRT). We use the Mt. Gorsa quarry (Trentino, Italy) as a field laboratory to upscale a physics-based approach, which was developed in the laboratory, to in situ conditions, including the effects of fracture heterogeneity, environmental conditions and IRT limitations. We reconstructed the slope in 3D using UAV photogrammetry, characterized the rock mass quality in the field at selected outcrops in terms of the Geological Strength Index (GSI) and measured their cooling behavior through 18h time-lapse IRT surveys. With ad hoc field experiments, we developed a novel procedure to correct IRT data in outdoor environments with complex topography. This allowed for a spatially distributed quantification of the rock mass surface cooling behavior in terms of a Curve Shape Parameter (CSP). Using non-linear regression, we established a quantitative CSP-GSI relationship, which allowed for the CSP to be translated into GSI maps. Our results demonstrate the possibility of applying infrared thermography to the slope-scale mapping of rock mass fracturing based on a physics-based experimental methodology.